2002
DOI: 10.1046/j.1365-2958.2002.02860.x
|View full text |Cite
|
Sign up to set email alerts
|

HSF and Msn2/4p can exclusively or cooperatively activate the yeast HSP104 gene

Abstract: SummaryIn an effort to understand how an accurate level of stress-specific expression is obtained, we studied the promoter of the yeast HSP104 gene. Through 5¢ deletions, we defined a 334 bp fragment upstream of the first coding AUG as sufficient and essential for maximal basal activity and a 260 bp fragment as sufficient and essential for heat shock responsiveness. These sequences contain heat shock elements (HSEs) and stress response elements (STREs) that cooperate to achieve maximal inducible expression. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 63 publications
2
58
0
Order By: Relevance
“…2kbProOsClpB-cyt::Gus rice seedlings in this study showed expression of Gus in response to treatment with Co, Cd, and As. In yeast, Grably et al (2002) noted that the appropriate transcription of Hsp104 is usually obtained through cooperation between the Msn2/4/STRE and the Hsf/ HSE systems and that each factor could activate the promoter alone, backing up the other. Fine mapping of the elements underlying the response to heat and metals in the OsClpB-cyt promoter remains to be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2kbProOsClpB-cyt::Gus rice seedlings in this study showed expression of Gus in response to treatment with Co, Cd, and As. In yeast, Grably et al (2002) noted that the appropriate transcription of Hsp104 is usually obtained through cooperation between the Msn2/4/STRE and the Hsf/ HSE systems and that each factor could activate the promoter alone, backing up the other. Fine mapping of the elements underlying the response to heat and metals in the OsClpB-cyt promoter remains to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from HSEs, metal stress responsive elements (STREs) are present in HS promoters. STREs are shown to be important in recruiting metal toxicity specific transcription factors such as MTF-1 in yeast (Grably et al 2002).…”
Section: Noted That the Induced Response To Hs Is Lost If The Canonicmentioning
confidence: 99%
“…Recently, Grably et al (41) reported that transcriptional control of HSP104 is achieved exclusively or cooperatively through activation of heat shock elements and stress response elements. So, we examined the effect of GTS1 gene dosage on the transcription of HSP104 and other genes tested above in response to heat shock.…”
Section: Effect Of Gts1p On Transcription Of Genes Of Hsps and Trehalmentioning
confidence: 99%
“…Gts1p tagged with His 6 at the carboxyl terminus was overexpressed in yeast, and the purified protein was named Gts1p-His 6 . DNA fragments of the upstream sequence of HPS104 ranging from Ϫ271 to Ϫ1 (probe 1) and from Ϫ380 to Ϫ192 (probe 2), with respect to the A of the initiation codon of HSP104, were used as probes, because Grably et al (41) reported that a 334-bp fragment upstream of the first coding AUG is sufficient and essential for maximal basal activity. We tested the gel-shift assay under various binding conditions and found that neither probe formed any complexes with Gts1p-His 6 except for a faint signal that was also found for His 6 as a control (Fig.…”
Section: Fig 8 Subcellular Localization and The Protein Level Of Gtmentioning
confidence: 99%
“…tially among different heat-shock genes, causing Hsf1p HSF activity must be tightly controlled to avoid inapand Msn2p/4p to have distinct contributions to the propriate expression of heat-shock proteins (Nollen heat-induced expression of these genes (Treger et al and Morimoto 2002). Thus, HSF is negatively regu-1998; Boy- Marcotte et al 1999; Amoros and Estruch lated, kept in an inactive or low activity conformation 2001; Grably et al 2002).…”
mentioning
confidence: 99%